To the mathematical theory of representation of information in neural nets - Zaritskii, A. F. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study irreducible nonorthogonal resolutions of the identity. The results obtained show that, in contrast to traditional requirements of “independent measurements” type, the noncommutative approach gives a more precise description of information systems.